Crypto Deep Ring Topology Firewall in Sensitive Data Transmission and Retrieval in Cloud - Vikas K. Soman; V. Natarajan (IET Information Security)
The data transmission and data retrieval process from the cloud is a critical issue because of cyber-attacks. The data in the cloud is highly vulnerable and may fall prey to hackers. The hackers tend to attack the data in the public network, deteriorating the range of confidentiality and the authentication of the data. To prevent this attack on the cloud data, this manuscript proposes a crypto deep ring topology firewall to protect the cloud from data breaches. The data transmission has been performed using egress ring topology crypto encryption that solves the difficulty in isolating the traffic path between the edge and cloud network. Moreover, during the cloud data retrieval, the data interoperability issue arises due to the improper cloud service level agreement, which is solved using an application programing interface firewall fetch intrusion prevention system used in the secure transmission technique in which the data are entered into the transport and session layer of the firewall and then into the intrusion detection and prevention system thus sieving of data is carried out to solve the amenability violation of the cloud network and eliminate data interoperability issue. The proposed model was implemented in the Python platform and provided an enhanced level of encryption and decryption performance than the existing cloud retrieval model, producing high access speed to the cloud network with data security. The proposed work has proved to be highly robust against cyber attacks like man-in-the-middle attacks and spoofing attacks.